Find New RoadsTM? A Systematic Review on the Impacts of Off-Road Vehicle Activity on Soil, Vegetation, and Wildlife - Ploughe, Laura W.; Fraser, Lauchlan H. (Frontiers in Ecology and Evolution, 2022)
The use of off-road vehicles (ORVs) in natural environments around the world has accelerated rapidly over the last few decades, resulting in significant social and environmental consequences. As the demand, use, and promotion of light-duty ORVs like all-terrain vehicles (ATVs), motorcycles, four-wheel drive trucks and sport utility vehicles (SUVs) increases in remote wilderness, the landscape is becoming fragmented into disorganized and destructive networks of trails and roads. This growth in ORV activity can result in substantial ecological impacts to a wide range of ecosystem structures and functions. Applying a global systematic review, we explore 105 publications about plant, soil, and wildlife responses to ORV traffic in different habitats to help guide the direction of future research, monitoring programs, and mitigation efforts. Most studies explored impacts to animals, followed by soils, then vegetative responses. Of the soil studies, most focused on physical impacts to the soil (i.e., compaction, erosion, rut dept), although there is some indication that ORV traffic may impact chemical and other edaphic properties. Vegetation loss was the primary focus on plant response to ORV activities, although impacts on the plant community were also investigated. Animal studies included impacts of ORV use on invertebrates, mammals, birds, and to a lesser extent reptiles/amphibians, including population-level, community-level, and behavioral responses. Overall, research on environmental impacts of ORV traffic is biased to coastal and desert ecosystems in the northern hemisphere (primarily in the US), often does not address the mechanisms that may produce ecological impacts (e.g., intensity of vehicular disturbance and ecosystem- or species-specific sensitivity to ORV activities), and frequently focuses on short-term responses. More research is needed to understand the mechanisms that cause the different responses of soil, plant, and animals to ORVs over the long-term in a broad range of ecosystems to support real-time management and conservation efforts.